Being watched: legal challenges to government surveillance - Vagle, Jeffrey L. (New York University Press, 2017)
You are being watched -- A history of government surveillance -- Getting through the courthouse door -- The doctrine of Article III standing -- Before the Supreme Court -- Government surveillance and the law -- The legacy of Laird v. Tatum -- Technology, national security, and surveillance -- The future of citizen challenges to government surveillance